Jawabanmu

2014-03-10T21:00:46+07:00
F(3) = -7
3a+b = -7 ..... persamaan (1)

f(-2) = 8
-2a+b = 8 ..... persamaan (2)

Eliminasi 2 persamaan tersebut :
3a+b = -7
-2a+b = 8
___________ -
5a = -15
a = -3

Substitusi persamaan 1 :
3a+b = -7
3(-3)+b = -7
b = 2

Fungsi f(x) = -3x+2
f(-10) = -3(-10)+2
f(-10) = 32

  • Iwan
  • Gemar Membantu
2014-03-10T21:02:36+07:00
F(3) = 3a + b = -7
f(-2) = -2a + b = 8
______________ -
5a = -15
a = -3
3a + b = -7
-9 + b = -7
b = -7+9
b = 2
terima kasih :)
f(-10) = -10*-3+2= -30+2 = -28